A Review of Comparative Advantage Assessment Approaches in Relation to Aquaculture Development - Junning Cai; PingSun Leung (Blackwell Publishing, 2025)
The economic concept of comparative advantage can be a useful methodology in providing valuable information for both commercial and policy decision making regarding aquaculture development. This paper appraises two approaches commonly used in the economics literature for comparative advantage assessment. One is the domestic resource costs (DRC) approach; and the other is the revealed comparative advantage (RCA) approach. Several aquaculture-related empirical applications of the DRC and RCA approaches are reviewed. Finally, the respective merits and problems of these two complementary approaches and how they could be used to provide policy guidance are outlined.